Senior house officers and their training. I. Personal characteristics and professional circumstances. Issue 6710 (18th November 1989) - Grant, J.; Marsden, P.; King, R. C.
Abstract : To assess the experience and perceptions of training of senior house officers in medicine a population survey of senior house officer training was conducted on senior house officers, registrars, senior registrars, and consultants in six medical specialties in South East Thames region by interview and postal questionnaire. The overall response rate was 72%, varying from 62% to 83% according to status and from 61% to 80% according to specialty. Although most of the 226 senior house officer respondents were aged 28 or under (168/225), had been qualified for four years or less (168/225) and were British (176/223), a quarter were older and had been qualified for five years or more; in all, 17 other nationalities were represented. Twenty two were aged over 33, and 17 had been qualified for more than 10 years. Thirty five senior house officers worked more than the mode of the distribution of duty rotas (one in three). Among postgraduate qualifications achieved or pursued, those related to general practice were highly represented (164 examinations); 111 senior house officers intended becoming general practitioners, 63 non-teaching hospital consultants, and 34 university or NHS teaching staff. Analysis of career progression showed that an appreciable number (31/221) had had more than three senior house officer posts. The findings indicate that the main implications for training and education are time for study, careers advice, and revision of educational programmes.